2016
DOI: 10.1007/s12325-016-0324-7
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Radioembolization with Yttrium-90 for the Treatment of Hepatocellular Carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is a common cause of worldwide mortality. Transarterial radioembolization (TARE) with yttrium-90 (Y90), a transcatheter intra-arterial procedure performed by interventional radiology, has become widely utilized in managing HCC.MethodsThe following is a focused review of TARE covering its commercially available products, clinical considerations of treatment, salient clinical trial data establishing its utility, and the current and future roles of TARE in the management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 66 publications
(80 reference statements)
1
104
1
Order By: Relevance
“…A cost-benefit analysis demonstrated that TACE is billed at $17,000 versus $31,000 or $48,000 for unilobar or bilobar TARE, respectively. 8,9 CUrrenT DaTa On Tare are liMiTeD, anD FUrTHer sTUDies are neeDeD TO BeTTer DeFine iTs rOle in THe TreaTMenT OF HCC There are unique circumstances when TARE may be preferred over TACE (e.g., the presence of portal vein thrombosis or the need to induce hypertrophy of unaffected segments prior to surgical resection). 8,10 However, without more robust data, TARE cannot be uniformly endorsed.…”
mentioning
confidence: 99%
“…A cost-benefit analysis demonstrated that TACE is billed at $17,000 versus $31,000 or $48,000 for unilobar or bilobar TARE, respectively. 8,9 CUrrenT DaTa On Tare are liMiTeD, anD FUrTHer sTUDies are neeDeD TO BeTTer DeFine iTs rOle in THe TreaTMenT OF HCC There are unique circumstances when TARE may be preferred over TACE (e.g., the presence of portal vein thrombosis or the need to induce hypertrophy of unaffected segments prior to surgical resection). 8,10 However, without more robust data, TARE cannot be uniformly endorsed.…”
mentioning
confidence: 99%
“…Automated image analysis may reduce errors from manual analysis (2)(3)(4). Specifically, in abdominal imaging, liver segmentation has multiple direct potential clinical applications, including automated liver volume measurement, which is an important prognostic metric for hepatic surgical procedures (5)(6)(7)(8)(9), and determination of radiation dose in liver tumor radioembolization (10). Other emerging applications include quantification of proton density fat fraction (PDFF) from multiecho MRI examinations to assist in the diagnosis and management of nonalcoholic fatty liver disease (NAFLD) and assessment of liver morphology to assist in the detection of liver cirrhosis (11,12).…”
mentioning
confidence: 99%
“…TARE-Y90 was well tolerated ( Table 2) TARE-Y90 is commonly utilized in adult patients with unresectable primary or secondary liver malignancies, and has been shown to be superior to transarterial chemoembolization in terms of time-toprogression of disease, toxicity profile, and posttreatment quality of life in adults with hepatocellular carcinoma. 15 In the adult population, TARE-Y90 has led to improved survival and has been used for downstaging patients prior to liver transplantation. [16][17][18] It is accepted treatment in the National Comprehensive Cancer Network guidelines for hepatobiliary cancer 19 and neuroendocrine tumors.…”
Section: Diagnoses Are Presented Inmentioning
confidence: 99%